2020
DOI: 10.1542/peds.2020-034637
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Use in Caries Prevention in the Primary Care Setting

Abstract: Dental caries remains the most common chronic disease of childhood in the United States. Caries is a largely preventable condition, and fluoride has proven effectiveness in caries prevention. This clinical report aims to clarify the use of available fluoride modalities for caries prevention in the primary care setting and to assist pediatricians in using fluoride to achieve maximum protection against dental caries, while minimizing the likelihood of enamel fluorosis. Fluoride varnish application is now conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…The AAP recommends a first dental visit by age 1 year. [25][26][27] The American Dental Association recommends that children be seen by a dentist within 6 months of eruption of the first tooth and no later than age 12 months. It also recommends 2.26% fluoride varnish for children younger than 6 years who are at risk for developing dental caries.…”
Section: Recommendations Of Othersmentioning
confidence: 99%
“…The AAP recommends a first dental visit by age 1 year. [25][26][27] The American Dental Association recommends that children be seen by a dentist within 6 months of eruption of the first tooth and no later than age 12 months. It also recommends 2.26% fluoride varnish for children younger than 6 years who are at risk for developing dental caries.…”
Section: Recommendations Of Othersmentioning
confidence: 99%
“…Around 1% of the area's natural water sources are estimated to contain fluoride concentrations greater than 2 mg/L. [43]. Fluoride levels may be elevated in northern Thailand due to geothermal water sources [44].…”
Section: Discussionmentioning
confidence: 99%
“…(22) Even in the US and other developed countries, dental caries continues to be a major chronic disease of childhood. (23) A previous cross-sectional study conducted among a group of Egyptian children and published in 2021, has shown that some children suffered from distinct visual changes in enamel only without breakdown according to the Caries Assessment Spectrum and Treatment index system (CAST). These carious lesions could have been prevented or reversibly and non-invasively managed by fluoride which has a preventive and remineralizing effect on hard tooth structure (24) .…”
Section: Discussionmentioning
confidence: 99%